(untitled) (Journal of the College of Basic Education, 2023)
The problem of this research is how the Iraqi actor deals with the dramatic character in Epic Theater (Brecht); Especially those in the play (The Good Man fromszwan); Is the treatment consistent with the propositions (Brecht) on non-reincarnation beforeactor 0 and stand out character; and bystander dimensions to match or sympathize withPersonal ; Rather, look at it critically. The research aims to know the propositions (Brecht) about how the actor treats the characterdramatic; And the approach of the Iraqi representative from that way; For theatrical characters(The good person from Setzwan) which was directed by (Awni Karumi) for the two bands of the Art TheaterModern and popular theatre. In the first topic of the theoretical framework of the research, the researcher deals with what (personality) is.In general, and what is the (dramatic character) in particular, and discusses the opinions of psychologists in this regard;Foremost among them is Freud. In the second topic, the researcher discusses the propositions of (Bertolt Brecht).about his epic theatre; and about his dramatic characters; And the foundations on which I buildPersonal ; and its representative treatment; The actor is more like a narrator for the characterIt is characterized by its own characteristics. Brecht rejects the psychological box of personality.That is, the actor should not adopt the character’s actions; Rather, it allows the spectator to look foralternatives. and that personality does not represent an individual in society; Rather, it represents a particular social class or organization.